PERBANDINGAN PENEMPATAN PANEL FOTOVOLTAIK DI ATAS TANAH (GROUND MOUNTING PV) ATAU DI ATAS ATAP (ROOFTOP PV) SEBAGAI IMPLEMENTASI PEMANFAATAN PLTS YANG EFISIEN DI ITERA - Syamsyarief Baqaruzi; Kiki Kananda; Ali Muhtar (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2020)
The use of photovoltaic panels (PV) as the latest material technology to conversion solar energyinto electrical energy, so as it can become a Solar Power Plant (PLTS) which is more continues to growin this world, including Institut Teknologi Sumatera (ITERA). As a new campus technology-based inLampung Province which also has high solar potential, it is considered appropriate to be able to applyphotovoltaic as the key to the use of renewable energy. The PV panel studied is a comparison with theplacement conditions, specifically placement on the rooftop and on the groundmounting. In order to getthe best efficiency from the comparison of the installed photovoltaic panels, it is necessary to design anequivalent circuit with a load or no load in designing, as well as making observations for 7 days withthe same conditions. The results show that the placement of PV on the rooftop is 1,129.91 Wh for aloaded condition and 3,961.91 Wh for a no-load condition, while the placement of PV on thegroundmounting is 1,064.83 Wh for a loaded condition and 3,880.13 for a no-load condition. Fromthese results, it becomes the basis for the placement of PV as needed before planning the constructionof PLTS.